Portuguese and talian: a case study of three generations’ perceptions and realities - Seimetz, Amanda (Universidade do Vale do Rio dos Sinos, 2019)
Officially, Brazil is recognized as a bilingual country, having Portuguese and LIBRAS as its two national languages. However, many other languages being spoken in the country, one of them being Talian. This research has the objective of presenting the perceptions of three generations of the same family of Talian speakers, surrounding its usage, relevance, and the need for the language to be passed on along. The intent is to describe how these speakers see Talian, either as a language or variety of Italian, and to develop a better knowledge around the possible future of the language in the community, based on the participant’s views. The three participants are members of a Portuguese-Talian bilingual family; they answered questionnaires and were invited to take part in interviews. The aim is to describe, based on the data collected, how each participant sees and interacts with Talian. The research and works developed by Harding‐Esch, E., Riley, P. (2003), Bloomfield (1933), Romaine (1995), Baker (2001), Myers - Scotton (2006), Grosjean (1996), De Fina (2007), King and Mackey (2007), Lambert (1980), Poplack (1980), Spolsky (2004) and Ferguson (1949) were of great value in helping develop the theoretical basis and the data analysis of what was collected. According to the viewpoint of the participants, it is possible to affirm that Talian is seen as a language and that it is predominantly an oral language.
Keywords: Bilinguismo; Língua minoritária; Política linguistica; Talian; Bilingualism; Linguistic policy; Minority language